Developing Traditional Food Supply Chains to Support Food Independence and Security: NRBV, MICMAC and ISM Approaches - Achmad, Lukman; Sahid Sujiwo, Aryo (Spektrum Industri, 2026)
Traditional food SMEs play a crucial role in driving the economy, preserving cultural heritage, and supporting food security. However, they face numerous challenges in building sustainable supply chains, including limited knowledge of the roadmap for developing them. This study aims to develop a conceptual hierarchy model that can guide traditional food SMEs in developing a Natural Resources-based View (NRBV)-based supply chain. This study employed a mixed-methods survey to collect and analyze data to answer the research questions. The surveyed companies were eight traditional food processing companies in West Bandung Regency, West Java Province. The study involved 12 expert respondents and 64 consumers as data sources, and employed the Delphi process, MICMAC, and Interpretative Structural Modeling (ISM) as data analysis methods. The analysis identified 13 key success factors relevant to developing an NRBV-based supply chain for traditional food SMEs. Of these factors, four factors categorized as dependent factors (association/professional support, green financing, raw material management, logistics system, and consumer development), three factors categorized as connecting factors (human resource quality, supplier development and environmentally friendly packaging), and five factors categorized as independent factors (information technology implementation, green technology adoption, government policies and support, company leadership commitment, and pollution prevention and waste management). The results of the study provide implications for the importance of waste management, product management, and sustainability in building a sustainable supply chain in traditional food SMEs.